QUALITY CHARACTERISTICS OF SURFACE WATERS AT ASPROLAKKAS RIVER BASIN, N.E. CHALKIDIKI, GREECE - Kelepertzis, E.; Argyraki, A.; Daftsis, E.; Ballas, D. (Bulletin of the Geological Society of Greece, 2010)
The present study reports on a four sampling period (April 2008-July 2008-November 2008-February 2009) study of water quality in streams of NE Chalkidiki. A total of 80 surface water samples were collected and analysed for the major ions Ca2+, Mg2+, K+, Na+, Cl- , HCO3 - , SO4 2-, NO3 - and the trace elements Pb, Fe, Cd, Cu, Cr, Ni, Zn, Mn and As. Also pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Temperature, as well as the stream water discharge at each sampling point, were determined in the field. The treatment and the subsequent evaluation of the data showed that the water samples are divided into three separate groups, reflecting the chemistry of water in the three sub-basins of the area i.e., Kokkinolakkas, Kerasia and Piavitsa. The water of the first one is possibly affected by the past mining activities of the area, whereas samples from the other two reflect the influence of sulphide mineralization on the hydrogeochemistry of the corresponding streams. No effect of the seasonal differentiation of stream water discharge was observed.